2017
DOI: 10.1128/mbio.01246-17
|View full text |Cite
|
Sign up to set email alerts
|

Revitalization of a Forward Genetic Screen Identifies Three New Regulators of Fungal Secondary Metabolism in the Genus Aspergillus

Abstract: The study of aflatoxin in Aspergillus spp. has garnered the attention of many researchers due to aflatoxin's carcinogenic properties and frequency as a food and feed contaminant. Significant progress has been made by utilizing the model organism Aspergillus nidulans to characterize the regulation of sterigmatocystin (ST), the penultimate precursor of aflatoxin. A previous forward genetic screen identified 23 A. nidulans mutants involved in regulating ST production. Six mutants were characterized from this scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 75 publications
3
45
0
Order By: Relevance
“…Production of both mycotoxins was recovered by the complement strain, although not to the level of the control strain, which was in agreement with gene expression analysis (Figures 2A-D). These results were not totally unexpected considering that previous publications have reported similar outcomes, where the complement strains partially restored the parental phenotype (Carvalho et al, 2010;Kwon et al, 2011;Pfannenstiel et al, 2017).…”
Section: Sntb Modulates Mycotoxin Biosynthesissupporting
confidence: 84%
See 1 more Smart Citation
“…Production of both mycotoxins was recovered by the complement strain, although not to the level of the control strain, which was in agreement with gene expression analysis (Figures 2A-D). These results were not totally unexpected considering that previous publications have reported similar outcomes, where the complement strains partially restored the parental phenotype (Carvalho et al, 2010;Kwon et al, 2011;Pfannenstiel et al, 2017).…”
Section: Sntb Modulates Mycotoxin Biosynthesissupporting
confidence: 84%
“…Most studies investigated the role of histone modifying enzymes, such as methylases or histone deacetylases in modulating secondary metabolite synthesis in fungi. However, more recently an additional histone modifying protein, the epigenetic reader SntB, was identified in Aspergillus species to regulate not only fungal development and secondary metabolism (Pfannenstiel et al, 2017) but also virulence in the aflatoxigenic fungus A. flavus (Pfannenstiel et al, 2018). SntB orthologs, called Snt2, had previously been described in the plant pathogens Fusarium oxysporum (Denisov et al, 2011) and Magnaporthe oryzae (He et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some genes with potential roles in boosting dothistromin production are present on chromosome 11, although these duplications were shared with two other strains: USA12 (lowest dothistromin producer) and SAF4 (high producer). Amongst these genes, Ds75171 is an orthologue of A. nidulans AN5169 (Boi1), a phospholipid binding protein gene recently implicated in regulation of secondary metabolism (Pfannenstiel et al ., ). Another gene present on chromosome 11 that could facilitate high levels of dothistromin production is a putative major facilitator superfamily (MFS) transporter gene Ds75255.…”
Section: Resultsmentioning
confidence: 97%
“…S5), which indicated that it was a new functional protein. The protein in P. fici consisted of 730 amino acids encoded by 2779 nucleotides, with three putative introns and a possible Aspergillus nidulans homologue of this protein (AN4699) has just been reported, but no clear function was described (Pfannenstiel et al, ). Collectively, these results show that RsdA is a new conserved regulator in fungi.…”
Section: Resultsmentioning
confidence: 99%